Stable, Intended HPLC Method for the Determination of Mirabegron and its Impurity in Solid Dosage form - Ganpisetti Srinivasa Rao,; K. Basavaiah,; P. Sunil Reddy,; L. Kalyanaraman,; B. M. Rao1 Rajkumar Sundaram, (International Journal of Pharma and Bio Sciences, 2021)
Mirabegron is used to treat the overactive bladder (OAB) in adults to urge urinary incontinence like leaking or wetting accidents. Patients may have feeling such as urinate right away, urinating more often than usual. The objective of this study was to develop a simple method to evaluate the known impurities in Mirabegron. HPLC instrument has auto sampler, column oven module, variable wavelength detector modules connected to Empower software computer. Method validation was performed for all parameters and results were satisfactory. Precision, linearity, accuracy, specificity, ruggedness and robustness were performed. Precision results confirmed the method and system precision results are within the limit similarity factor for two standards between 0.98 to 1.02 and six replicate test solution results (%RSD) are found to be below 2.0%. Method validation results confirmed that the method can be used to check the product quality during product manufacturing.